Β2‐Adrenergic stimulation enhances Ca2+ release and contractile properties of skeletal muscles, and counteracts exercise‐induced reductions in Na+–K+‐ATPase Vmax in trained men. (13th November 2014) - Hostrup, M.; Kalsen, A.; Ørtenblad, N.; Juel, C.; Mørch, K.; Rzeppa, S.; Karlsson, S.; Backer, V.; Bangsbo, J.
Abstract : Key points: From animal models, it is well established that β2 ‐adrenergic stimulation increases contractile force, rates of Ca 2+ release and uptake from the sarcoplasmic reticulum, and Na + –K + ‐ATPase activity of skeletal muscles. However, these effects are unexplored in humans. Here we report that β2 ‐adrenergic stimulation with the high dose selective β2 ‐adrenoceptor agonist terbutaline elicits positive inotropic and lusitropic effects on non‐fatigued m. quadriceps that are associated with enhanced rates of Ca 2+ release and uptake from the sarcoplasmic reticulum in trained men. However, we also observed that the positive inotropic and lusitropic effects of β2 ‐adrenergic stimulation on m. quadriceps were blunted when muscle fatigue developed. Furthermore, we show that β2 ‐adrenergic stimulation counteracts exercise‐induced reductions in Na + –K + ‐ATPase V max (maximum rate of activity) and elevates glycolytic activity during high intensity exercise. These findings are important for our understanding of the role of β2 ‐adreceptor activation in regulation of ion handling and contractile properties of non‐fatigued and fatigued skeletal muscles in humans. Abstract: The aim of the present study was to examine the effect of β2 ‐adrenergic stimulation on skeletal muscle contractile properties, sarcoplasmic reticulum (SR) rates of Ca 2+ release and uptake, and Na + –K + ‐ATPase activity before and after fatiguing exercise in trained men. The study consisted of two experiments (EXP1, n  = 10 males, EXP2, n  = 20 males), where β2 ‐adrenoceptor agonist (terbutaline) or placebo was randomly administered in double‐blinded crossover designs. In EXP1, maximal voluntary isometric contraction (MVC) of m. quadriceps was measured, followed by exercise to fatigue at 120% of maximal oxygen uptake ( V ̇ O 2, max ). A muscle biopsy was taken after MVC (non‐fatigue) and at time of fatigue. In EXP2, contractile properties of m. quadriceps were measured with electrical stimulations before (non‐fatigue) and after two fatiguing 45 s sprints. Non‐fatigued MVCs were 6 ± 3 and 6 ± 2% higher ( P  < 0.05) with terbutaline than placebo in EXP1 and EXP2, respectively. Furthermore, peak twitch force was 11 ± 7% higher ( P  < 0.01) with terbutaline than placebo at non‐fatigue. After sprints, MVC declined ( P  < 0.05) to the same levels with terbutaline as placebo, whereas peak twitch force was lower ( P  < 0.05) and half‐relaxation time was prolonged ( P  < 0.05) with terbutaline. Rates of SR Ca 2+ release and uptake at 400 nm [Ca 2+ ] were 15 ± 5 and 14 ± 5% ( P  < 0.05) higher, respectively, with terbutaline than placebo at non‐fatigue, but declined ( P  < 0.05) to similar levels at time of fatigue. Na + –K + ‐ATPase activity was unaffected by terbutaline compared with placebo at non‐fatigue, but terbutaline counteracted exercise‐induced reductions in maximum rate of activity ( V max ) at time of fatigue. In conclusion, increased contractile force induced by β2 ‐adrenergic stimulation is associated with enhanced rate of Ca 2+ release in humans. While β2 ‐adrenergic stimulation elicits positive inotropic and lusitropic effects on non‐fatigued m. quadriceps, these effects are blunted when muscles fatigue.